MODEL-MODEL PENELITIAN UNTUK PERBAIKAN MUTU PENDIDIKAN BAHASA ARAB - Iswanto, Rahmat (BELAJEA: Jurnal Pendidikan Islam, 2016)
This article examines how the quality of arabic education to be developed in order to improve the quality of arabic education implementation. Then finally the result will be an evaluation of the model of research that needs to be implemented furthermore.Arabic education department which is a branch of developing education in the field of arabic language, is an institutional part of the Islamic university that focuses on how the implementation of the arab language education can be implemented well.With a good implementation, the quality of its department will be good as well.The sources data of data analysis is academic researches in the post graduate program ofarabic education of UIN Malang.It also identifies problems with dimensions affecting Arabic Education.The results of this article conducted by post-graduate student of Arabic Education with the obtained samples wastendency 74.1 % of descriptive tipes of researches.33.3 % of researches were about âspeakingâ, 80.8 % of researches were not specifically for the elements of language skill, 91.0 % of researcheswere not specific to a particular science, 42.0 % of researches studied on learning methods and strategies, 45.9 % of researcheswere on high school level and 87.5 %of researcheswere about public schools.